Structural features of nucleoli in blood, leukemic, lymphoma and myeloma cells - Smetana, K (European journal of histochemistry, 2002)
At present, it seems clear that the nucleolus is multifunctional and represents one of the key cell organelles that participate directly or indirectly in cell resting, proliferation, differentiation and maturation states, and possibly also in programmed cell death. Thus, the morphology and cytochemistry of nucleoli may represent a very useful tool not only for the evaluation of nucleolar biosynthetic activities but also for the evaluation of various cell states under physiological, experimental and pathological conditions.
Keywords: Leukemia; Cell Nucleolus; krevní buňky; lidé; Blood Cells; Multiple Myeloma; lymfom; Lymphoma; mnohočetný myelom; buněčné jadérko; leukemie; Humans